Navigating autonomy, competence, and relatedness: Insights from middle managers in Norway - Kristin Spieler Severinsen (Administrative Sciences, 2024)
Middle managers play a pivotal role in bridging the gap between senior leadership and employees, often navigating competing demands and pressures. This study investigates experiences of autonomy, competence, and relatedness among middle managers serving as department heads in the University and University College (UUC) sector in Norway. The study adopts a qualitative approach in the form of semi-structured interviews with six participants. The findings underscore the significance of autonomy, trust, and support in facilitating the effective execution of middle managers' roles as executive and inclusive leaders. Autonomy emerges as crucial, which aligns with the principles of the Nordic work-life model. Furthermore, the study highlights the importance of internal motivation and the support provided by the immediate leadership in enhancing middle managers' performance. Personal competence in one's subject areas and relatedness emerge as key factors ensuring employee confidence and fostering a positive work environment. The implications of these findings suggest that nurturing autonomy, competence, and relatedness may mitigate the perceived stress associated with being a middle manager in the UUC sector. By addressing these fundamental needs, organisations can potentially enhance the well-being and effectiveness of middle managers, ultimately contributing to organisational success.
Keywords: 350; middle managers; autonomy; competence; relatedness; self-determination theory